KELEMBAGAAN KELOMPOK TANI HUTAN DI KECAMATAN BARUSJAHE KABUPATEN KARO SUMATERA UTARA - br Ginting, Laura Julita; Batubara, Ridwanti; Herianto, Herianto (Program studi Kehutanan USU, 2015)
Institutional has an important role in supporting the people’s forest management. The institution started from a group which has the same characteristics and purpose. The purpose of this study is to know the institutional system of forest farmer groups in the forest management, such as land management activities, structural and cultural aspects, institutional objectives, membership and leadership, and institutional capacity in the Rumanis Village, Pertumbuken Village, and Sikab Village. The results of this research showed that the land management activities include: land cleanup and nurseries, weeding, replanting, thinning, and fertilization. Leader in select based professionalism owned by the leadership. Institutional system of forest farmers groups in district of Barusjahe has the same purpose to reduce deforestation and made members better. Institutional capacity is still as organizer of counseling and help to solved the problems of farmers. Keywords: Institutional, Farmers Group, Forest